Effect of crude palm oil (CPO) and changes of temperature towards the asphalt mixture strength - Abdul Qayyum, Samsuddin (2017)
The purpose of this study is to determine whether by adding crude palm oil (CPO) as an additive to the warm mix asphalt can reducing the temperature without compromise the strength of the asphalt mixtures. The strength of the asphalt mixtures can be determined from the stability, air void and also density which can be obtained in the Marshall Test. There are 60 asphalt mixtures that are provided with different temperature and percentage of crude palm oil (CPO) which are l20°C, 130°C, 140°C, 150°C, 160°C and 170°C and 0.3% and also 0.5% respectively. The gradation for aggregate used in this mixture is AC14. The maximum weight for total mixing of the aggregates used is 1200g while the grade for bitumen is 80/100 for penetration test. The results of this analysis can be used to investigate and compare the strength of the asphalt mixtures between the warm mix asphalt and hot mix asphalt. The outcome of this lab results is to compare whether by adding the crude palm oil (CPO) to warm mix asphalt mixtures can reducing the temperature and sustain the same strength of asphalt mixtures. The findings may be useful to change from hot mix asphalt to warm mix asphalt.